The Use of Advanced Technologies in the Performance of Geoinformatic Work - Muzaffarovich, Abdullaev Ashraf; Yarashovich, Sattorov Shahzod; Jaxongir, Kamolov; Abdullo, Akhrorov; Askar, Ochilov (European Journal of Life Safety and Stability (2660-9630), 2021)
This article provides information on the use of advanced technologies in the performance of Geodetic and geoinformatic work, as well as the advantages of this software.